Meningkatkan Kemampuan Guru dalam Melaksanakan Penilaian Autentik melalui Kegiatan Supervisi Akademik - Defi Nofalia (Journal on Education, 2023)
Authentic assessment carried out at SMPN 5 Muntok. In the learning process there are still deficiencies caused by teachers in the learning process have a tendency. Non-test assessment techniques that can more comprehensively measure learning outcomes tend to be. These problems through mentoring teachers through academic supervision in teaching management, starting from planning, implementing the teaching and learning process, to evaluation. The purpose of this study was to improve teacher performance in learning at SMP Negeri 5 Muntok. This research method is action research carried out in two cycles. The results of research on improving teacher performance in the preparation of lesson plans as a whole is that in the pre-cycle it was 75% after the first cycle action became 82%, and after the second cycle action it increased again to 96%. For the implementation of learning to increase teacher performance as a whole, it was in the pre-cycle of 77% after the first cycle action became 84%, and after the second cycle action increased again to 91% (very good category).